IPTEKS BAGI MASYARAKAT DESA MLATIHARJO MENUJU PENGELOLAAN KOMODITAS DESA BERBASIS DIGITAL - Suprihadi Suprihadi; Radius Tanone; Rudy Latuperissa (Universitas Raharja, 2018)
Mlatiharjo is a village in Demak District, Central Java province, it has been well-known as an innovative village because of their various innovations especially in high quality (supreme) seed varieties of fruit and rice. In order to support the production and cultivation of those commodities, information management has been employed but still in simple ways and doesn’t have any information system yet, therefore it often causes mistake in their production estimation. It will impact to their sales service of their commodities toward the buyer, particularly the customer. Another problem is Mlatiharjo’s farmer group does not have any information exchange medium to interact with other business actors who comes from outside their area, whereas those outsider-business actors will buy their product with a higher price. Mlatiharjo’s IbM Program aims to build an Information System which is able to manage the information of Mlatiharjo’s commodities production, especially in farming production. The method employed for developing the system is Prototyping. Meanwhile, the transfer of technology employs mentoring process for the client of program through conducting focus group discussion, workshop dan training. This Commodity Information System is implemented into two kinds of computer application. Firstly, web application that is used for managing the data center and share it to the public who want to capture the information of the mlatiharjo’s product. Secondly, android based mobile application utilized by the farmer who has become a member of cluster-farming group to input the location area mapping data and progress report of production data and also provide a discussion forum among member of the system. The Web Application is built using PHP and the database used MySQL. Mobile Application is implemented using Java Android. As a result, Tani Mahardika Cluster and KSU Citra Kinaraya – Mlatiharjo have a digital-based system to manage their Commodity in order to encourage and strengthen business-production institution through Commodity Information System